LITERATURE – MUSIC – VISUAL ARTS: INTERMEDIATE INTERPRETATION OF THE TEXTIN PRE-SCHOOL EDUCATION - Siderova, Dеsislava (E-Journal VFU, 2025)
The study presented is focused on students from master's programs in preschool pedagogy. The possibilities of texts from different sign systems for joint functioning within the situation as a form of pedagogical interaction with preschool children are considered. The preferences of graduate students for interaction are outlined between texts of different semiotic basis in their asynchronous functioning based on a primary literary text.
Keywords: arts; intermediality; interdisciplinarity